The Reinforcement of Multiculture-Based Curriculum For Students of Foreign Nationalities in Indonesian Schools - Rachmawati, Iva (Universitas Negeri Semarang, 2015)
Multicultural curriculum in Indonesia is developed for students with multicultural backgrounds to internalize multicultural values without having to lose their own cultural identity. A multicultural curriculum is designed to promote teaching methods developed based on the diversity of the students themselves with the purpose of educating them to understand pluralism, humanism, and democracy and to respect each other both inside and outside the school. Such a multicultural curriculum proves to be a barrier for students with non multicultural backgrounds. Â Their different backgrounds limit their understanding of the diversity. This situation requires a new curriculum. This article is the result of the Competitive Grants research regarding multicultural curriculum for students of foreign nationalities. The interviews with the participants of IACS (Indonesian Art & Culture Sholarship) program in 2013 and 2014 have indicated that classroom discussions and direct interaction with the local community could become some kind of reinforcement for the formation of a new curriculum for students with foreign nationalities to better understand the diversity of Indonesia instead of art and cultural education.